1998
DOI: 10.1164/ajrccm.157.5.9709020
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Induces Apoptosis in Malignant Mesothelioma Cells

Abstract: Malignant mesothelioma causes profound morbidity and nearly universal mortality that is refractory to conventional treatment with aggressive surgery, radiotherapy, or chemotherapy. We report that pharmacologic concentrations of lovastatin, a 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitor, induced apoptosis in human malignant mesothelioma cell lines. Mesothelioma cell viability was decreased in a dose-dependent manner by lovastatin (5 to 30 microM). These effects were not reversed by exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 27 publications
1
52
1
Order By: Relevance
“…We and others have reported that the HMG-CoA reductase inhibitor lovastatin induces apoptosis of a variety of tumor cells including acute myelogenous leukemia, 9 medulloblastoma, 10 mesothelioma, 11 and neuroblastoma. 12 Recently, we have shown that lovastatin also induces significant apoptosis in a large number of tumor-derived cell lines including juvenile monomyelocytic leukemia, pediatric solid malignancies (rhabdomyosarcoma, medulloblastoma) and squamous cell carcinoma of the cervix and of the head and neck.…”
Section: Introductionmentioning
confidence: 93%
“…We and others have reported that the HMG-CoA reductase inhibitor lovastatin induces apoptosis of a variety of tumor cells including acute myelogenous leukemia, 9 medulloblastoma, 10 mesothelioma, 11 and neuroblastoma. 12 Recently, we have shown that lovastatin also induces significant apoptosis in a large number of tumor-derived cell lines including juvenile monomyelocytic leukemia, pediatric solid malignancies (rhabdomyosarcoma, medulloblastoma) and squamous cell carcinoma of the cervix and of the head and neck.…”
Section: Introductionmentioning
confidence: 93%
“…The HMG-CoA reductase inhibitors or statins, therefore, have pleiotropic biological and physiological effects on cell functions. Notably, statins have been shown to induce apoptosis in many cell lines [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Blockage of protein geranylgeranylation is believed to be the major mechanism for statin induction of apoptosis [4][5][6][7][8][9][10][11]. Therefore, targeting at protein geranylgeranylation could have an important role in anti-carcinogenesis [1,2,13].…”
Section: Introductionmentioning
confidence: 99%
“…3 The isoprenylation of Ras proteins is critical for their cellular function and inhibition of isoprenylation abolishes the transforming activity of mutated Ras proteins. 4 Lovastatin, one of the statins that has also been found to arrest tumor and normal cells in G1 phase of the cell cycle, 5,6 induced a potent apoptotic response [7][8][9][10] and has been demonstrated to exert antitumor effects in mice. [11][12][13][14][15] In several studies using murine melanoma models, lovastatin was shown to have antitumor effects both when used alone 12 or in combination with other agents.…”
mentioning
confidence: 99%